Unpalatable Truths: Food and Drink as Medicine in Colonial British India. (13th March 2018) - Goodman, Sam
Abstract: This article considers the significance of eating and drinking within a series of diaries and journals produced in British colonial India during the Indian Rebellion of 1857. The discussion of food and drink in this context was not simply a means to add color or compelling detail to these accounts, but was instead a vital ingredient of the authors' understanding of health and medical treatment. These texts suggest a broader colonial medical understanding of the importance of regulating diet to maintain physical health. Concern with food, and the lack thereof, was understandably a key element in diaries, and in the eyewitness accounts kept by British soldiers, doctors, and civilians during the rebellion. At a narrative level, mention of food also functioned as a trope serving to increase dramatic tension and to capture an imagery of fortitude. In references to drink, by contrast, these sources reveal a conflict between professional and lay opinions regarding the use of alcohol as part of medical treatment. The accounts show the persistent use of alcohol both for medicinal and restorative purposes, despite growing social and medical anxieties over its ill-effects on the body. Close examination of these references to food and drink reflect the quotidian habits, social composition, and the extent of professional and lay knowledge of health and medicine in colonial British India.